Strategi Komunikasi Mandorumah dalam Mewujudkan Eksistensi Slogan Kontraktor Anti Molor - Yanto, Heri; Mirza, Mochammad; Hardiyanti , Rini (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The prevalent cases of stalled contractors have drawn attention within the construction industry. However, Mandorumah, a contracting company, has taken a different approach as the